Political parties: electoral change and structural responce - "Ware, Alan (ed.)" (New York, 1987)
In recent years political parties have been under pressure from a variety of sources changes in social and economic structures, a revolution in election campaign technology, declining participation in parties. In this timely contribution to one of the most important areas of comparative politics a collection of experts on different countries focus on the political parties themselves their structures, intra party relations, financial arrangements and voter-party links. The regimes covered range from those in which one party is dominant but still has to organize itself to fight elections because of the possibility of voter defection to those where a fully competitive party system applies.
Keywords: Political parties